On the possibility of a cash-like CBDC - Hanna Armelius; Carl Andreas Claussen; Isaiah Hull (Sveriges Riksbank, 2021)
We explain why all CBDCs will need a ledger that keeps track of CBDC ownership regardless of whether they are “token-based”, “DLT-based” or “on a blockchain”; and regardless of how we define these terms. Consequently, token-based CBDCs appear not to have a greater capacity for providing payments that are peer-to-peer, offline or anonymous like cash than “account-based” CBDCs.
Keywords: E42; E51; 330; CBDC; Tokens; Offline